Lesson Study in Early Years Education: Collaborations through Freedom - ไกรสรพงษ์ คำแก้ว (วารสารการจัดการทางการศึกษาปฐมวัย, 2019)
The purpose of the lesson study was to give teachers, school administrators and parents a practical understanding that collaborations in early years immerge when given freedom. Through lesson study we hope for the teachers, school administrators and parents to gain a greater understanding of freedom in the early years’ education and to recognize the importance of freedom and how it enables collaborations among young children. Participants in the study included mixed-age groups of children ages 2-8 years old, teachers, school administrators, and parents. The project spanned over a period of nine weeks in nine thematic summer camp programs during April-May 2017. The results of the lesson study came from the analyzation of detailed photos taken of the students working on their projects and the reflections of the parents on those photos. The results were: (1) In free and relaxing outdoor environment students became motivated, independent and joyful learners, (2) In mixed-age groupings, where students were given freedom, collaborations among children occurred naturally, (3) Children learn best from each other; they became self-motivated, independent, confident, obtained higher self-esteem, and were enthusiastic learners. The lesson learned in this Lesson Study Project for the teachers, school administrators and parents were a practical understanding that through freedom of movement, exploration, social interactions, choice, as well as freedom from the interference of others, children became motivated, independent, confident, enthusiastic, joyful learners, who also obtained higher self-esteem and that collaborations in early years immerge naturally when given freedom.